ЕНЕРГОЕФЕКТИВНІ ТЕПЛОНАСОСНІ ТЕХНОЛОГІЇ. СТАН ТА ПЕРСПЕКТИВИ ЇХ ВПРОВАДЖЕННЯ В УКРАЇНІ - Sniezhkin, Yu.F. (Institute of Engineering Thermophysics of NAS of Ukraine, 2017)
In the article addresses issues the state, development and implementation of heat pump technology in Ukraine. Examples use of these technologies both in the world and in Ukraine. Presented various schemes using of heat pump technology in field of housing economy and industry. Shown volume are possible economy of power resources in a wide implementation of heat pump technology.